Prunus avium L. (Sweet Cherry) By-Products: A Source of Phenolic Compounds with Antioxidant and Anti-Hyperglycemic Properties—A Review - Nunes, Ana R. (2021)
Prunus avium L. (sweet cherry) is one of the most appreciated fruits due to its organoleptic and nutritional value. Interestingly, cherry leaves, stems, and flowers are agri-food by-products rich in bioactive compounds that are mostly still unexploited. Stems and leaves have been used in folk medicine since ancient times. Recently, cherry flowers have also proved to be an interesting source of compounds with therapeutic properties. Phenolic compounds, namely hydroxycinnamic acids and flavonoids, are the most present phytochemicals in P. avium fruits and their by-products. These compounds have shown a good antioxidant potential to prevent oxidative stress-related diseases and glycemic control, fundamental in preventing and controlling diabetes mellitus. The present review summarizes the main phenolics found in P. avium stems, leaves, and flowers as compared to their fruits and describes their antioxidant and anti-hyperglycemic properties. Thus, these by-products are an accessible and low-cost source of bioactive constituents with interesting health-promoting properties, making their use promising in diabetes therapy.